2015
DOI: 10.1021/jacs.5b06814
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of Active Oxygen Species in Fe-Containing Ni-Based Oxygen Evolution Catalysts: The Effect of pH on Electrochemical Activity

Abstract: Ni-based oxygen evolution catalysts (OECs) are cost-effective and very active materials that can be potentially used for efficient solar-to-fuel conversion process toward sustainable energy generation. We present a systematic spectroelectrochemical characterization of two Fe-containing Ni-based OECs, namely nickel borate (Ni(Fe)-B(i)) and nickel oxyhydroxide (Ni(Fe)OOH). Our Raman and X-ray absorption spectroscopy results show that both OECs are chemically similar, and that the borate anions do not play an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

53
459
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 521 publications
(516 citation statements)
references
References 55 publications
53
459
2
2
Order By: Relevance
“…30 What is different between the observations here and in ref. 29, and the report by Trześniewski et al is that the "active oxygen" species was observed along with the oxidation of Ni 2+ to Ni 3+ , as indicated by UV-vis and XAS data, whereas the additional oxide species in our study and, likewise, the Raman peak at 560 cm -1 in ref.…”
Section: Operation Of the Thin Film Electrochemical Cellcontrasting
confidence: 77%
“…30 What is different between the observations here and in ref. 29, and the report by Trześniewski et al is that the "active oxygen" species was observed along with the oxidation of Ni 2+ to Ni 3+ , as indicated by UV-vis and XAS data, whereas the additional oxide species in our study and, likewise, the Raman peak at 560 cm -1 in ref.…”
Section: Operation Of the Thin Film Electrochemical Cellcontrasting
confidence: 77%
“…The oxide can sustain local positive/negative charges on the surface, as discussed in Section 2, which allows decoupled pathways (i.e., PT and ET) to occur. An example of the decoupled ET and PT path for the OER is reported by Koper, Smith, and co‐workers 152, 153. In situ surface‐enhanced Raman spectroscopy was employed in their study, the spectra of which indicate the presence of superoxo‐type species formed by the PT step 153.…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 90%
“…In contradistinction to an Fe active site model for Fe:Ni oxides, although Mössbauer studies of Fe:Ni layered double hydroxides provide direct evidence for the formation of Fe 4+ in Fe:Ni oxide catalysts during OER, these Fe 4+ sites do not account for the observed catalytic activity (24). Moreover, the formed "active oxygen" species have been found to be adsorbed on nickel sites in Fe:Ni films in borate buffer (25)(26)(27), suggesting Ni centers as active sites for OER. These results together suggest that the presence of Fe active sites may not be the primary reason for the enhanced activity of Fe:Ni catalysts films and point to another chemical role for Fe in oxidic Ni films.…”
mentioning
confidence: 77%